Characterizing impulsivity and resting‐state functional connectivity in normal‐weight binge eaters. Issue 3 (23rd December 2019) - Oliva, Rossella; Morys, Filip; Horstmann, Annette; Castiello, Umberto; Begliomini, Chiara
Abstract: Objective: Binge eating is characterized by episodes of uncontrolled eating, within discrete periods of time. Although it is usually described in obese individuals or as a symptom of Binge Eating Disorder (BED), this behavior can also occur in the normal‐weight (NW) population. An interesting premise suggests that impulsivity might contribute to the onset of binge eating and the progression toward weight gain. Drawing upon this evidence, here we explored impulsivity in NW individuals reporting binge‐eating episodes through a functional connectivity approach. We hypothesized that, even in the absence of an eating disorder, NW binge eaters would be characterized by connectivity pattern changes in corticostriatal regions implicated in impulsivity, similarly to the results described in BED individuals. Methods: A resting‐state functional magnetic resonance imaging study tested 39 NW men and women, with and without binge eating (binge eaters, BE and non‐BE). Brain functional connectivity was explored by means of graph theoretic centrality measures and traditional seed‐based analysis; trait impulsivity was assessed with self‐report questionnaires. Results: The BE group was characterized by a higher degree of trait impulsivity. Brain functional connectivity measures revealed lower degree centrality within the right middle frontal gyrus, left insula/putamen and left temporoparietal regions and a lower functional connectivity between the right middle frontal gyrus and right insula in the BE group. Discussion: The results support previous evidence on BED of altered functional connectivity and higher impulsivity at the roots of overeating behavior, but further extend this concept excluding any potential confounding effect exerted by the weight status.